Propiedades quimiopreventivas de Passiflora mollissima (Kunth) L. H. Bailey (curuba larga) contra cáncer colorrectal (2015)
ABSTRACT: Passiflora mollissima (Kunth) L. H. Bailey (banana passion fruit), a fruit that contains polyphenolic compounds and high reducing capacity, with few information about their benefits on the prevention of colorectal cancer. Objectives: evaluate the effect of regular consumption of curuba in the prevention of Colorectal Cancer in a preclinical experimental model induced with azoxymethane. Methods: chemopreventive activity of banana passion fruit was estimated counting Aberrant Crypt Foci in the colon of mice when the fruit was administered before and after the induction of colon cancer with the agent azoxymethane. The total phenols, flavonoids and carotenoids content was determined by spectrophotometric methods. The antioxidant capacity by FRAP (Ferric Reducing/Antioxidant Power) DPPH and ORAC (oxygen radical absorbance capacity) methods. Results: banana passion fruit regular ingesting has dose-dependent effect on the reduction of Aberrant Crypt Foci in the studied model in vivo. The phenol content was: 460.1 mg. Gallic acid/100 g dried fruit; the flavonoid content: 1907.6 mg Catechin/100 g of dried fruit, and carotenoid content: 118.8 mg β -caroteno/100 g dried fruit. FRAP value: 8520.31 mg equivalent/100 g ascorbic acid, DPPH 60843.11 μmol Trolox Equivalent/100g dried fruit, ORAC 20962.60 μmol Trolox/100g dried fruit. Conclusions: banana passion fruit has phenolic and carotenoid compounds, presents antioxidant capacity, and reduces the formation of Aberrant Crypt Foci.